Polygenic Risk Score of Longevity Predicts Longer Survival Across an Age Continuum. (20th November 2020) - Tesi, Niccolo'; van der Lee, Sven J; Hulsman, Marc; Jansen, Iris E; Stringa, Najada; van Schoor, Natasja M; Scheltens, Philip; van der Flier, Wiesje M; Huisman, Martijn; Reinders, Marcel J T; Holstege, Henne
Abstract: Studying the genome of centenarians may give insights into the molecular mechanisms underlying extreme human longevity and the escape of age-related diseases. Here, we set out to construct polygenic risk scores (PRSs) for longevity and to investigate the functions of longevity-associated variants. Using a cohort of centenarians with maintained cognitive health ( N = 343), a population-matched cohort of older adults from 5 cohorts ( N = 2905), and summary statistics data from genome-wide association studies on parental longevity, we constructed a PRS including 330 variants that significantly discriminated between centenarians and older adults. This PRS was also associated with longer survival in an independent sample of younger individuals ( p = .02), leading up to a 4-year difference in survival based on common genetic factors only. We show that this PRS was, in part, able to compensate for the deleterious effect of the APOE-ε4 allele. Using an integrative framework, we annotated the 330 variants included in this PRS by the genes they associate with. We find that they are enriched with genes associated with cellular differentiation, developmental processes, and cellular response to stress. Together, our results indicate that an extended human life span is, in part, the result of a constellation of variants each exerting small advantageous effects on aging-related biological mechanisms that maintain overall health and decrease the risk of age-related diseases.